In silico population analysis of the CLOCK rs3749474T-rs4864548A haplotype and its relationship with obesity - Flores Carrasco, Sergio.; Olguín Barraza, Mariela.; Roco Videla, Ángel Gerardo. (Medwave Estudios, 2023)
It has been suggested that the rs3749474T/rs4864548A haplotype of the CLOCK gene increases the risk of obesity, but the population variability of these alleles and the haplotype is unknown. This research aims to determine the linkage between the rs3749474T and rs4864548A alleles from the database of 1000Genomes to confirm the existence of the TA haplotype polymorphisms of these alleles and their frequency in five macro populations. Linkage disequilibrium and haplotype frequencies for 2504 individuals from 26 populations were analyzed using the r2 statistic and Fisher's exact test. There is a high frequency of the TA haplotype in Latin America (44.8%), a high linkage disequilibrium (r2= 0.92) worldwide between these alleles, a high differentiation between macro populations, and a high homogeneity. The evidence warrants further studies on the association between this haplotype and the risk of obesity and overweight in Latin American populations.
Análisis poblacional in silico del haplotipo CLOCK rs3749474T-rs4864548A y su relación con obesidad
Keywords: Haplotypes; Linkage disequilibrium; Period circadian proteins; Obesidad